An Evaluation of Certain Cognitive Aspects of the Material Objects Unit of the Science Curriculum Improvement Study Elementary Science Program. - Allen, Leslie R. (Journal of Research in Science Teaching, 1970)
The article presents a study investigating the performance of first grade children involved in the Science Curriculum Improvement Study elementary science program, which is funded by the U.S. National Science Foundation, in Honolulu, Hawaii. The superiority of their performance was compared to non-participants in the program using a Static-Group Comparison design. The difference in the performance was found to be minimal. Thus, it was observed that superior exploratory behavior cannot be easily determined after only one year in the program. The author states that cumulative effect of the program can be successfully measured at the sixth level.